Reflections on a phenomenological inquiry into Zimbabwean women's stories of managing schools - Muzvidziwa, Irene (2016)
This paper reflects on the importance of applying a phenomenological approach to women’s lived experiences as educational leaders. This paper draws its data mostly from fieldwork conducted in 2004/5 in Zimbabwe. The research was an in-depth qualitative study that was conducted along phenomenological lines with an emphasis on rich contextual detail. The paper explores issues relating to how women educational leaders experienced leadership roles, their perceptions of their roles and the challenges they faced and how they dealt with those challenges.